Comparative Analysis of PowerPoint-Enhanced vs. Traditional Lecture Methods on Anatomy Learning Outcomes in Nursing Education at Bishop Shanahan Hospital, Nsukka, Enugu State - Okpa, Stella E.; Iheanacho, Peace N.; Ingwu, Justin A.; Madu, Obageli T.; Nwanyia, Ebere J. (European Journal of Applied Sciences, 2025)
The learning of anatomy by nurses demands that student nurses acquire basic knowledge and skills through effective teaching methods. This study aimed to investigate the effectiveness of PowerPoint-enhanced lectures and traditional teaching methods on anatomy learning outcomes in nursing education at Bishop Shanahan Hospital, Nsukka, Enugu State. A pretest-posttest quasi-experimental design was used for the study, with all 51 Preliminary Training Studies (PTS) students admitted for the 2023–2024 academic session as respondents. The Anatomy Assessment Test (AAT) questionnaire was the main instrument used for data collection. Data analysis was performed via IBM SPSS version 25. The results revealed that the performance of the students at pretest and posttest was 10.66±2.93 and 34.09±5.88, respectively, when using PowerPoint-enhanced lectures (PPEL) and 13.66±3.04 and 34.26±6.67, respectively, when using traditional teaching methods (TTM). A significant difference was observed between PPEL and TTM in terms of their effectiveness on the performance of the students, “p = 004”. PowerPoint-enhanced lecture was more effective at improving the academic performance of nursing students than the traditional lecture method.